Distribution and Population Status of Embelia ribes Burm. F., a Red Listed Medicinal Plant in India, and its Relevance in Conservation - Geetha, S.; Haridasan, K.; Krishnamurthy, K. V.; Mujeeb, C. A. (Indian Forester, 2014)
Field surveys were undertaken to various parts of India to study distribution and population status of Embelia ribes, a red listed medicinal plant of India, used in many Ayurveda preparations, which also forms an important NTFP. Although this species has been reported across the country, it was never seen in great abundance during the present study and was often restricted to clearings and forest paths in the evergreen and semi-evergreen forests. Variation in leaf size and shape as well as fruit size were also observed in E. ribes collected from different locations. There are differences in fruiting and non-fruiting plants with respect to floral structure.